THE ROLE OF SCHOOL AND TEACHING METHOD THROUGH MARIA MONTESSORI AND JOHANN HEINRICH PESTALOZZI`S VIEW - Sofni Indah Arifa Lubis (CERED Indonesia Institute, 2021)
The development of each child must be observed. The education and teaching methods need to be adjusted to the child’s development. Montessori and Pestalozzi are early childhood education experts who opened-up the eyes to a new way of teaching method in the golden age stages in children. This study examined Montessori’s and Pestalozzi`s concepts on early childhood education. Pestalozzi believed empowering individual skills can improve the society, capable of knowing what is right and what is wrong and of acting according to this knowledge. On the other hand, Montessori believed that children have power to learn naturally and challenge themselves to do something big and to live independently. This research used library approach. The results showed that both experts agreed on (1) the cognitive, affective, and psycho-motoric aspects of a child needs to be stimulate, (2) learning environment should be structured in a so the children can learn naturally, and (3) teachers are required to become observers. These patterns of education put children as the subject of teaching method. Both methods are applicable and expected to be able to maximize in shaping the children`s character at their golden ages.